Socio-Political Situation of Alania on Eve of Mongol Conquest - E. V. Kaziev (Научный диалог)
The relevance of the study is determined by the consideration of the issues of the socio-political structure of the medieval Alanian state, which are one of the debatable in modern alanistics, which is manifested mainly in the use of regressive or progressive approaches in interpreting the political system of Alania, as well as in the use of various approaches in describing its political structure. The avoidance of these approaches in the interpretation of social and political orders in Alanya during the period under review has become a scientific novelty of the study. As a result, it was concluded that the basis of the socio-political structure of Alania in the first forty years of the XIII century was a specific combination of forms of the suzerain-vassal hierarchy and patriarchal-tribal democracy, with weak political unity, supported by the presence of a common ruling dynasty, but in reality it was a conglomerate of several territorial and tribal possessions formed by a network of unilocal consanguineous collectives capable of being part of wider internal political associations formed on the basis of the principle of artificial kinship, which, perhaps, were similar in structure to the sworn brotherhoods known in the Caucasus until the middle of the 19th century.